2021
DOI: 10.3389/fimmu.2021.712722
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the NKG2D Receptor-Ligand Axis Using CRISPR: Novel Technologies for Improved Host Immunity

Abstract: The activating immune receptor natural killer group member D (NKG2D) and its cognate ligands represent a fundamental surveillance system of cellular distress, damage or transformation. Signaling through the NKG2D receptor-ligand axis is critical for early detection of viral infection or oncogenic transformation and the presence of functional NKG2D ligands (NKG2D-L) is associated with tumor rejection and viral clearance. Many viruses and tumors have developed mechanisms to evade NKG2D recognition via transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 197 publications
0
2
0
Order By: Relevance
“…The mutual recognition and cross-linking of the MIC molecule and the NKG2D receptor enable immune cells to recognize and attack the emerging stress cells externally. No MHC Class I expression or antigen recognition is required; Therefore, it can be said that the MIC/NKG2D interaction is an effective immune surveillance mechanism [37] .…”
Section: Nkg2dmentioning
confidence: 99%
“…The mutual recognition and cross-linking of the MIC molecule and the NKG2D receptor enable immune cells to recognize and attack the emerging stress cells externally. No MHC Class I expression or antigen recognition is required; Therefore, it can be said that the MIC/NKG2D interaction is an effective immune surveillance mechanism [37] .…”
Section: Nkg2dmentioning
confidence: 99%
“…Aside from MHC Class I, EMT-TFs have previously been shown to activate the inhibitory immune receptors killer Ig-like receptors (KIR) KIR3DL1, KIR2DL1, KIR2DL3, and KIR2DL4 [145], and repress activating immune-receptor natural killer group member D (NKG2D) ligands UL-16 binding protein (ULBP) 1 [146] and ULBP2 [147] on the tumor cell surface. Interestingly, Lopez-Soto and colleagues [147] showed that induction of EMT in colorectal cancer cells via SNAIL overexpression induced upregulation of the NKG2D ligands MICA/B and ULBP2, suggesting an avenue for NKG2D-mediated natural killer (NK) cell immunotherapy [148]. However, follow-up experiments identified that levels of soluble MICA were also elevated in the SNAIL-activated tumors, which act as a decoy to limit anti-cancer surveillance by NK cells.…”
Section: Emt-tfs Facilitate Immune Evasionmentioning
confidence: 99%